Progression on Citrullination of Proteins in Gastrointestinal Cancers - Song, Shuzheng; Yu, Yingyan (Frontiers in Oncology, 2019)
The citrullination modification (Cit) of proteins has received increasing attention in recent years. This kind of protein modification was first discovered in autoimmune diseases such as rheumatoid arthritis. The citrullination modification process is catalyzed by the peptidyl arginine deiminases (PADIs) family. A well-known citrullination of histone involves the key mechanism of neutrophil extracellular traps (NETs) of inflammation in the peripheral blood. Further studies revealed that citrullination modification of proteins also involves in carcinogenesis in human being. Citrullinated proteins disturbed the stability of proteins and caused DNA damages. There is increasing evidence that citrullinated proteins can be used as potential targets for cancer diagnosis or treatment. This review introduces the concept of citrullination modification of proteins, substrate proteins, examining methods and biological significances.